Buletin Peternakan : PENGARUH PEMBERIAN JAGUNG KUNING FERMENTASI DENGAN SUPLEMENTASI POLYUNSATURATED FATTY ACID (PUFA) DAN L-KARNITIN TERHADAP DAYA TETAS TELUR PUYUH - Ayu Siswoyo Putri, Sudibya, Ratih Dewanti (Peternakan UGM, 2015)
The aim of the research was to evaluate the effect of feeding fermented yellow corn withÃ‚ polyunsaturated fatty acid and L-Karnitin supplementation on the hatchability of quail (Coturnix-coturnixÃ‚ japonica) egg. A number of 160 female and 40 male quails of 70 days old were used as experimental animal. The present research was designed in oneway Completely Randomized Design (CRD) with five treatments and four replication, each replication contains of eight female and two males quails